Giant anteater (Myrmecophaga tridactyla) conservation in Brazil: Analysing the relative effects of fragmentation and mortality due to roads. (December 2018) - Pinto, Fernando A.S.; Bager, Alex; Clevenger, Anthony P.; Grilo, Clara
Abstract: Road networks can have serious ecological consequences for many species, mainly through habitat fragmentation and mortality due to collisions with vehicles. One example of a species impacted by roads is the giant anteater ( Myrmecophaga tridactyla ), currently listed as Vulnerable by IUCN. Here we analysed the relative effect of fragmentation and mortality due to roads on giant anteater populations and show the critical areas for their persistence in Brazil. We estimated minimum patch size and maximum road density to evaluate the impact of the road network and observed road-kills on this species. We explored different scenarios by varying values of dispersal capacity to estimate the minimum patch size, and also of population densities to estimate maximum road density for giant anteater persistence. Our findings indicated that the minimum patch size can be from 498 to 247 km 2 and the maximum road density can vary between 0.21 and 0.55 km/km 2 in pessimist and optimistic scenarios, respectively. In Brazil, habitat fragmentation seemed to have a major impact over giant anteater populations. Habitat fragmentation due to roads seemed to have a more negative effect than mortality due to collisions with vehicles. Critical areas for the species persistence can represent 32% of its range in the optimistic scenario with 18% of suitable patches below the minimum size and 0.1% above the maximum road density. This study provides insights and implications for road networks on giant anteater populations in Brazil and guidance on road density and patch size thresholds for land managers and road agencies charged with planning ecologically sustainable roads in Brazil. Highlights: Habitat fragmentation can be more detrimental than road-kills. Between 18% and 21% of suitable habitat is below the minimum patch size. Between 0.1% and 1% of species range is above the maximum road density. Critical areas for species persistence represent 32–36% of the species range. Conservation opportunities exist in northern areas while southern needs mitigation.